Eastern Germany's quality as a business location - Michael Krakowski; Dirk Lau; Andreas Lux (Intereconomics, 1993)
Private investment has a key role to play in the “economic take-off” in Eastern Germany. Can the region attract sufficient investment? What factors stand in the way of a rapid improvement in the quality of the new Länder as a location?
Keywords: 330; System Transformation